Integrated Reporting and Value Creation: the Semantics of the Fundamental Concept of Integrated Reporting - Marçal, Amanda dos Santos Veiga; Neumann, Marguit; Sanches, Simone Leticia Raimundini (Organizações & Sociedade, 2022)
The objective of this research is to build the semantics of the concept of value creation based on the existing literature, delimited to the Integrated Reporting (IR) proposal. It is a descriptive, bibliographic and documentary study, developed with use of content analysis. Sixteen articles, three books and one document were analyzed, based on the “Value Creation – Background Paper” (International Integrated Reporting Council, 2013a), as well as on the semantic classification proposed by Ilari and Geraldi (1985). The results show that the semantics of the concept of value creation is that the organization carries out actions of values (capitals) created directly or indirectly, considering only their positive effect on society and the environment. Negative actions cause value destruction for shareholders and stakeholders, and they are not reported when expected to be. Financial value is relevant, but not enough to create value. The absence of explanations on the subject makes it possible the non-adoption of the real purpose in the construction of the connectivity of financial and non-financial information, consequently damaging the credibility of this new corporate disclosure format. The research encourages discussions to fill gaps and counter criticisms, especially international ones. It contributes to the interpretation of the concept of value creation for future IR disclosures, clearly elucidating what would be the organization’s value creation and accountability to society, in view of the difficulty in applying this concept in public consultations (2013 and 2017), as revealed by preparers. This research also contributes to advancing the discussion in the literature in the value creation context.